Exchange of scanned documentation between social scientists and data archives: establishing an image file format and method of transfer - van der Meer, Cor; de Vries, Repke (IASSIST Quarterly, 1992)
Exchange of scanned documentation between social scientists and data archives: establishing an image file format and method of transfer